A randomized, single-blind trial of clobetasol propionate 0.05% cream under silicone dressing occlusion versus intra-lesional triamcinolone for treatment of keloid - Md Nor, Norazirah; Ismail, Rasimah; Jamil, Adawiyah; Shah, Shamsul Azhar; Imran, Farah Hani (Springer, 2017)
Background and Objective: Keloid is conventionally treated with intra-lesional (IL) triamcinolone, which is highly operator dependent and has its own adverse effects. Topical steroid and silicone dressings are a patient friendly and non-invasive treatment alternative. We therefore sought to determine the efficacy and safety of topical clobetasol propionate (Dermovate) 0.05% cream under occlusion with Mepiform silicone dressing compared to IL triamcinolone in the treatment of keloid. Methods: This was a prospective, randomised, observer-blinded study. Two keloids on the same site were randomly assigned to receive either daily topical clobetasol propionate 0.05% cream under occlusion with silicone dressing (Scar 1) or monthly IL triamcinolone injection (Scar 2). Efficacy was assessed using patient and observer scar assessment scale (POSAS) at 4-weekly intervals up to 12 weeks. Dimension of keloid and adverse effects were also assessed. Results: A total of 34 scars from 17 patients completed the study. There was significant improvement of POSAS at 12 weeks compared to baseline within each treatment group. However, there was no statistically significant difference in POSAS at 12 weeks between the two treatments. Keloid dimensions showed a similar trend of improvement by week 12 with either treatment (p = 0.002 in Scar 1, p = 0.005 for Scar 2). However, there was no significant difference between the treatment. In the IL triamcinolone group, all patients reported pain and 70.6% observed necrotic skin reaction. There was a significantly higher rate of adverse effects such as erythema (41.2 vs. 17.6%), hypopigmentation (35.3 vs. 23.5%), telangiectasia (41.2 vs.17.6%) and skin atrophy (23.5 vs. 5.9%) documented in the IL triamcinolone group when compared to clobetasol propionate 0.05% cream under occlusion with silicone dressing. Conclusion Clobetasol propionate 0.05% cream under occlusion with silicone dressing is equally effective and has fewer adverse effects compared to IL triamcinolone. Hence, it may be used as an alternative treatment for keloid particularly in patients with low pain threshold, needle phobia and those who prefers home-based treatment.